2015
DOI: 10.1007/s12187-015-9312-8
|View full text |Cite
|
Sign up to set email alerts
|

The Subjective Well-Being of School Children. The First Findings from the Children’s Worlds Study in Poland

Abstract: The paper presents the first findings of the children’s subjective well-being survey in Poland, which was conducted among representative sample of over 3000 pupils aged 8, 10 and 12 years from Wielkopolska region in spring 2014. The study is a part of International Survey of Children’s Well-being (ISCWeB) - Children’s Worlds, developed by the International Society for Child Indicators (ISCI). The main purpose of the ISCWeB project is to gain a broad knowledge of children’s lives, their relationships with famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 20 publications
4
37
0
1
Order By: Relevance
“…Personal factors such as internal control, self‐efficacy, and family and peer relationships are documented as factors affecting LS in children and adolescents (Park & Huebner, ). Relationships of LS with some demographic, genetic, cultural, and environmental variables are documented in some studies (Park, ; Park & Huebner, ; Strózik, Strózik, & Szwarc, ). Among demographic variables, the association of LS with age, grade level, and gender were not confirmed in several studies (Dew & Huebner, ; Huebner, ; Huebner, Drane, & Valois, ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Personal factors such as internal control, self‐efficacy, and family and peer relationships are documented as factors affecting LS in children and adolescents (Park & Huebner, ). Relationships of LS with some demographic, genetic, cultural, and environmental variables are documented in some studies (Park, ; Park & Huebner, ; Strózik, Strózik, & Szwarc, ). Among demographic variables, the association of LS with age, grade level, and gender were not confirmed in several studies (Dew & Huebner, ; Huebner, ; Huebner, Drane, & Valois, ).…”
Section: Introductionmentioning
confidence: 98%
“…In another study, children who lived in commercial areas in inner cities reported higher LS (Homel & Burns, ). In a study in Poland, the individual, family, school, friends, and living environment were five important domains of children's well‐being (Strózik et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…", "Yourself?". The scale has demonstrated acceptable internal consistency using Cronbach's alpha (α) across various contexts: In Algeria, the α ranged from .53 (10-years olds) to .66 (12 year olds) (Tiliouine 2015); in Italy (Migliorini et al 2019) α = .64 (8-year olds); in Brazil α = .69 with 9-13 year olds (Schütz et al 2018); in Poland with children aged 8, 10, and 12-year olds, α ranged from 0.64 to 0.76 (Strozik et al 2016); in India α = 0.82 with adolescents (x age= 16.05 years) (Hashim and Areepattamannil 2017); a longitudinal study with adolescents in the USA, found that at Time 1, α = .79 and at Time 2, α = .83 (Ng et al 2017); in Canada with a sample of youth (11-17 years old) with chronic health conditions α = 0.73, and parent report versions α = 0.81 (McDougall et al 2013), and finally cross-country comparative studies demonstrate acceptable reliability coefficients: α = .618 across Spain, South Africa, Algeria, and Israel (Gonzalez-Carrasco et al 2018), and ranging from .69 to .94 across 23 countries (Abubakr et al 2016).…”
Section: Brief Multidimensional Students' Life Satisfaction Scale (Bmmentioning
confidence: 99%
“…A survey of subjective well-being of children in Poland was conducted based on a representative sample of pupils aged 8, 10 and 12 as a part of the International Survey of Children's Well-Being (Strózik, Strózik & Szwarc, 2016). The degree of satisfaction with life demonstrated by children turned out to be high.…”
Section: Well-being Of Polish Adolescentsmentioning
confidence: 99%